Study on magnetic difference of artificial magnetite and natural magnetite. (November 2020) - Wang, Linjun; Chen, Tiejun; Cui, Jinbing; wei, Liu
Abstract: The magnetic differences of the artificial magnetite and the natural magnetite were studied to improve the magnetic parameters of artificial magnetite in the study. The effect of roasting conditions on the magnetism of artificial magnetite and the diffidence of magnetism and magnetic behavior of the artificial magnetite and natural magnetite was studied and compared. The results indicate that the magnetically strong artificial magnetite has been obtained under the optimized process parameters of the roasting temperature of 800°C, roasting time of 60min and the mass ratio of pulverized coal to ore (C/O ratio) of 2%. And the magnetic analysis shows that the magnetism of natural magnetite is stronger than that of artificial magnetite under the same conditions, but the remanence and coercivity of artificial magnetite is stronger than natural magnetite. With the decrease of particles, the magnetism of the artificial magnetite changes insignificantly, but the magnetization of natural magnetite decreases gradually; and the difference in the magnetism of two becomes smaller (from 1.53 × 10 -4 ·m 3 ·kg -1 to 0.14 × 10 -4 m· 3 ·kg -1 ) with the decrease of particles. The gaps and impurities in the ore are the cause of the difference, which provides a theoretical basis for the further study the size-fractionated magnetic separation of artificial magnetite.